PEDAGOGICAL AND PROFESSIONAL COMPETENCIES OF AQIDAH AKHLAK TEACHERS IN MANAGING THE LEARNING PROCESS MAN 2 MEDAN - Siregar, Bahtiar; Tumiran, Tumiran; Manshuruddin, Manshuruddin; Mardinsyah, Aziz (Proceeding International Seminar of Islamic Studies, 2024)
This research is an important contribution to thinking in the development of knowledge regarding the concepts and principles of implementing learning. The results of the research can be used as a means of understanding educational concepts in learning to better understand the character of each student, as well as providing functional education and learning services for students. Teachers must be fully competent (competent). constructing phenomena, and finding hypotheses. This research is the Pedagogical Competence of Islamic Religious Education Teachers in Managing Islamic Education Learning at MAN 2 Model Medan. The research results that will be obtained will not be through statistical procedures, but the discussion of this research will be packaged in the form of a description that describes the actual situation. Data collection techniques: observation, interviews, and documentation. The second way, the researcher carries out an analysis after collecting data in a certain period through three stages including: Data Reduction (Data Selection), Data Display (Data Presentation) and Conclusion Drawing/Vertification (Conclusion Drawing). Teachers understand and master the character of their students. Both from the physical aspect, moral aspect, spiritual aspect, social aspect and emotional aspect. This is done so that before learning takes place it can arouse students' enthusiasm and active learning. Learning takes place at school under direct teacher supervision. A teacher plays an important role as a person who is responsible for student development, namely by pursuing all their potential, both cognitive potential (knowledge), affective potential and psychomotor potential. For this reason, teacher behavior in the educational process should be developed. In such a way that it can have a positive influence on the educational process and results.